Eco-Friendly Fertilizer Shower Spreader from Maggot Waste: An Innovative Solution for Sustainable Agriculture in Rural Areas - Setyo Fiddin Wirabuana; Ahmad Muslim Haqiqi; Pramudya Mahaputra; Abdul Aziz (SAFARI :Jurnal Pengabdian Masyarakat Indonesia, 2025)
This study presents an innovative granular fertilizer spreader made from maggot waste, designed as an appropriate technology to improve agricultural efficiency and sustainability in Karyasari Village. The development process, using a participatory approach and a descriptive-qualitative method, aimed to address the common challenge of organic fertilizer distribution, especially for farmers with large fields but limited physical capacity due to age or health issues. The tool leverages nutrient-rich maggot residue, or frass, to ensure more uniform and efficient fertilizer application across vast agricultural lands. By utilizing frass, the tool not only provides an environmentally friendly solution by reducing the use of chemical fertilizers but also supports sustainable farming practices. Field trials conducted in the village revealed significant positive impacts. The innovation reduced the time to harvest by up to two weeks and increased crop yields by 20–30%, demonstrating its effectiveness in improving both agricultural productivity and efficiency. Additionally, this tool offers economic benefits, as it minimizes reliance on expensive chemical fertilizers, which are often financially burdensome for farmers in rural areas. Beyond its practical application in farming, the tool contributes to ecological benefits by promoting the use of local organic waste, such as maggot frass, as a resource. This process not only supports the sustainability of agriculture but also empowers rural communities by reducing waste and creating a more circular and resilient farming system. The findings highlight the potential of integrating appropriate technology with local organic waste as a strategic and effective approach for fostering sustainable agriculture in rural areas, ultimately contributing to both economic and environmental development. This innovation demonstrates how technology can serve as a key driver of rural empowerment and sustainable agricultural practices.